عصرِ حاضر میں الحادِ جدید کی صورتوں کا تحلیلی جائزہ: Analytical Review of Modern Atheism in the Contemporary Era - Farooq, Dr. Ghulam; Dr. Asma Aziz, Dr. Asma Aziz; Sajjad, Ms. Kinza (Al-Amīr Research Journal for Islamic Studies, 2024)
In the contemporary era, atheism has evolved, presenting new challenges and perspectives that significantly differ from traditional atheistic viewpoints. This article aims to conduct an analytical review of the various forms of modern atheism, exploring their origins, philosophies, and the factors contributing to their rise in the modern world. By delving into the sociopolitical, scientific, and philosophical landscapes that have fostered the growth of contemporary atheistic thought, this study seeks to understand the complexities and nuances of atheism today. The paper examines the impact of technological advancement, increased access to information, and the shifting paradigms of morality and ethics on the prevalence of atheism. Additionally, it explores how contemporary atheism interacts with religious beliefs, focusing on the dialogue and sometimes conflict between these differing worldviews. The analysis extends to the consequences of modern atheism on individuals and societies, considering both the emancipatory aspects and the existential challenges it poses. Furthermore, the article engages with various responses to modern atheism, including theological rebuttals, apologetics, and the efforts by religious communities to address the questions and critiques raised by atheistic thought. By providing a comprehensive overview of the landscape of modern atheism, this study contributes to a deeper understanding of its significance in the contemporary era and the ongoing discourse between belief and disbelief. Ultimately, this article seeks to offer a nuanced perspective on modern atheism, recognizing it as a multifaceted phenomenon that reflects broader changes in the global intellectual, cultural, and spiritual climate. Through this analytical review, the paper aims to facilitate a more informed and respectful dialogue between atheistic and theistic perspectives in the modern world. Key Words: Gnosticism, Agnosticism, Deism, Atheism, Theism, Secular, Modern Era.